Rapid recalibration of speech perception after experiencing the McGurk illusion - Claudia S. Lüttke; Alexis Pérez-Bellido; Floris P. de Lange (Royal Society Open Science, 2018)
The human brain can quickly adapt to changes in the environment. One example is phonetic recalibration: a speech sound is interpreted differently depending on the visual speech and this interpretation persists in the absence of visual information. Here, we examined the mechanisms of phonetic recalibration. Participants categorized the auditory syllables /aba/ and /ada/, which were sometimes preceded by the so-called McGurk stimuli (in which an /aba/ sound, due to visual /aga/ input, is often perceived as ‘ada’). We found that only one trial of exposure to the McGurk illusion was sufficient to induce a recalibration effect, i.e. an auditory /aba/ stimulus was subsequently more often perceived as ‘ada’. Furthermore, phonetic recalibration took place only when auditory and visual inputs were integrated to ‘ada’ (McGurk illusion). Moreover, this recalibration depended on the sensory similarity between the preceding and current auditory stimulus. Finally, signal detection theoretical analysis showed that McGurk-induced phonetic recalibration resulted in both a criterion shift towards /ada/ and a reduced sensitivity to distinguish between /aba/ and /ada/ sounds. The current study shows that phonetic recalibration is dependent on the perceptual integration of audiovisual information and leads to a perceptual shift in phoneme categorization.